Training and Implementation of Website as Digital Information Media at PKBM - Ahmad Gunawan; Dewa Saepurrahman (Universitas AMIKOM Yogyakarta, 2025)
Limited use of information technology in non-formal education institutions remains a challenge in delivering information to the public. PKBM Mandiri, as the partner in this activity, experienced difficulties in information dissemination, which was still carried out conventionally, resulting in limited service reach. This community service activity aims to improve the capability of administrators in utilizing digital media through website training and implementation. The methods applied include needs identification, website design and development, training implementation, and evaluation. The participants involved were PKBM administrators who directly engaged in the training process. The results indicate an improvement in participants’ understanding and skills in managing the website as an information medium. Furthermore, the website enhances information accessibility, improves communication effectiveness, and supports institutional promotion more efficiently. Overall, this activity contributes positively to improving the quality of digital-based information services at PKBM Mandiri.